Interaction of the model alkyltrimethylammonium ions with alkali halide salts: an explicit water molecular dynamics study - Druchok, M.; Podlipnik, Č.; Vlachy, V. (Condensed Matter Physics, 2013)
We present an explicit water molecular dynamics simulation of dilute solutions of model alkyltrimethylammonium surfactant ions (number of methylene groups in the tail is 3, 5, 8, 10, and 12) in mixture with NaF, NaCl, NaBr, and NaI salts, respectively. The SPC/E model is used to describe water molecules. Results of the simulation at 298 K are presented in form of the radial distribution functions between nitrogen and carbon atoms of CH₂ groups on the alkyltrimethylammonium ion, and the counterion species in the solution. The running coordination numbers between carbon atoms of surfactants and counterions are also calculated. We show that I- counterion exhibits the highest, and F- the lowest affinity to "bind" to the model surfactants. The results are discussed in view of the available experimental and simulation data for this and similar solutions.